Bank Helps Support Unsponsored Steelbands - Cardinez, Gary (Express)
Scotiabank’s managing director Richard Young challenged his competitors to come onboard and offer assistance to the steelband movement.
Keywords: Steel bands (Music) -- Trinidad and Tobago; Steel bands (Music) -- Finance -- Trinidad and Tobago; Scotiabank Trinidad and Tobago; Corporate sponsorship -- Trinidad and Tobago